Recovery and recrystallization effects on hydrogen transport behavior of V-Cu-Ni-Al hydrogen separation membranes - Han, Jung Hun; Song, Sang Yoon; Baek, Ju-Hyun; Nam, Jeong Hoon; Lee, Gunjick; Suh, Jin-Yoo; Sohn, Seok Su (Elsevier BV, 2026)
Vanadium-based alloys are promising candidates for hydrogen separation membranes due to their high hydrogen permeability and cost-effectiveness, but their practical application is hindered by hydrogen embrittlement and limited malleability. Among various alloy systems, dual-phase V–Cu alloys have emerged as promising alternatives, offering improved ductility and embrittlement resistance. However, while compositional design has been extensively investigated, the influence of thermally induced microstructural evolution on hydrogen transport remains insufficiently understood. In this study, a V76Cu15Ni2Al7 (at%) alloy was systematically examined to clarify how post-deformation annealing at 600–800 °C affects dislocation density, grain boundary character, and Cu precipitate morphology, and how these microstructural changes govern hydrogen diffusivity, solubility, and embrittlement behavior. Progressive recovery and partial recrystallization reduced dislocation density, while Cu precipitates underwent spheroidization and redistribution. These changes markedly enhanced hydrogen diffusivity (from 0.23 to 2.45 × 10−9 m2 s−1 at 400 °C) and permeability, while slightly reducing total solubility. Furthermore, the reduced hardness mismatch between the V and Cu phases alleviated interfacial stress concentration, thereby improving resistance to hydrogen embrittlement. Notably, membranes annealed at 800 °C maintained stable hydrogen permeation down to 125 °C without fracture. These findings establish that recovery, recrystallization, and precipitate redistribution are key microstructural levers for optimizing both hydrogen transport and long-term durability in V-based hydrogen separation membranes.